Color and hardness changes in artificial white spot lesions after resin infiltration - Ji-Hoon Kim; Ho-Hyun Son; Juhea Chang (Korean Academy of Conservative Dentistry, 2012)
Objectives The purpose of this study was to determine the effect of resin infiltration technique on color and surface hardness of white spot lesion (WSL) with various degrees of demineralization. Materials and Methods Ten human upper premolars were cut and divided into quarters with a 3 × 4 mm window on the enamel surface. Each specimens were separated into four groups (n = 10) and immersed in demineralization solution to create WSL: control, no treatment (baseline); 12 h, 12 hr demineralization; 24 h, 24 hr demineralization; 48 h, 48 hr demineralization. Resin infiltration was performed to the specimens using Icon (DMG). CIEL*a*b* color parameters of the enamel-dentin complex were determined using a spectroradiometer at baseline, after caries formation and after resin infiltration. Surface hardness was measured by Vickers Micro Hardness Tester (Shimadzu, HMV-2). The differences in color and hardness among the groups were analyzed with ANOVA followed by Tukey test. Results Resin infiltration induced color changes and increased the hardness of demineralized enamel. After resin infiltration, there was no difference in color change (ΔE*) or microhardness among the groups (p < 0.05). Conclusion There was no difference in the effect of resin infiltration on color and hardness among groups with different extents of demineralization.